Interplay between structure and magnetism in the low-dimensional spin system: K(C8H16O4)2CuCl3·H2O. Issue 7 (20th January 2017) - van Well, Natalija; Bolte, Michael; Delley, Bernard; Wolf, Bernd; Lang, Michael; Schefer, Jürg; Rüegg, Christian; Assmus, Wolf; Krellner, Cornelius
Abstract : The so far longest Cu–Cl bridging bonds of K(C8 H16 O4 )2 CuCl3 ·H2 O with 2 J exp = −23.78 cm −1 antiferromagnetic interaction between Cu–Cu are described in this article. Abstract : Materials based on a crown ether complex together with magnetic ions, especially Cu(ii ), can be used to synthesize new low dimensional quantum spin systems. We have prepared the new crown ether complex di-μ-chloro-bis(12-crown-4)-aquadichloro-copper(ii )-potassium, K(C8 H16 O4 )2 CuCl3 ·H2 O (1 ), determined its structure, and analyzed its magnetic properties. Complex (1 ) has a monoclinic structure and crystallizes in the space group P 21 / n with lattice parameters of a = 9.5976(5) Å, b = 11.9814(9) Å, c = 21.8713(11) Å and β = 100.945(4)°. The magnetic properties of this compound have been investigated in the temperature range 1.8–300 K. The magnetic susceptibility shows a maximum at 23 K, but no 3-D long range magnetic order down to 1.8 K. The S = 1/2 Cu(ii ) ions form antiferromagnetically coupled dimers with Cu–Cl distances of 2.2554(8) Å and 4.683(6) Å, and a Cu–Cl–Cu angle of 115.12(2)° with 2 J dimer = −2.96 meV (−23.78 cm −1 ). The influence of H2 O on the Cl–Cu–Cl exchange path is analyzed. Our results show that the values of the singlet–triplet splitting are increasing considering H2 O molecules in the bridging interaction. This is supported by density functional theory (DFT) calculations of coupling constants with Perdew and Wang (PWC), and Perdew, Burke and Ernzerhof (PBE) and the strongly constrained and appropriately normed (SCAN) exchange-correlation function show excellent agreement for the studied compound.